2021
DOI: 10.2217/nmt-2020-0059
|View full text |Cite
|
Sign up to set email alerts
|

CLICK-MS and MASTER-2 Phase IV Trial Design: Cladribine Tablets in Suboptimally Controlled Relapsing Multiple Sclerosis

Abstract: Cladribine tablets 10 mg (3.5 mg/kg cumulative dose over 2 years) are approved for the treatment of relapsing forms of multiple sclerosis (MS), including relapsing-remitting MS and active secondary progressive MS. However, real-world data on cladribine tablets are limited. CLICK-MS and MASTER-2 are single arm, observational, 30-month, Phase IV studies in the US evaluating the effectiveness and safety of cladribine tablets 3.5 mg/kg in patients with relapsing-remitting MS or active secondary progressive MS who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Subsequent clinical trials, clinical trials extensions, trial cohort follow-ups, and other studies have confirmed cladribine as a potent DMD for MS patients, with therapeutic efficiency lasting between 2-5 years or even up to 8 years in some individuals ( 29 , 42 , 44 49 ). Other ongoing clinical trials are aiming to further establish clear therapeutic indications for MS patients in various stages of the disease and clinical contexts ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent clinical trials, clinical trials extensions, trial cohort follow-ups, and other studies have confirmed cladribine as a potent DMD for MS patients, with therapeutic efficiency lasting between 2-5 years or even up to 8 years in some individuals ( 29 , 42 , 44 49 ). Other ongoing clinical trials are aiming to further establish clear therapeutic indications for MS patients in various stages of the disease and clinical contexts ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…PROs on the effectiveness and safety of cladribine tablets, including fatigue (through the 5-item version of Modified Fatigue Impact Scale), physical functioning (36-Item Short Form Health Survey), TSQM v1.4, and WPAI-MS, are also being evaluated as part of the CLICK-MS and MASTER-2 trials [ 28 ] and will provide a useful comparison with the results described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint is 24-month annualized relapse rate. Key secondary endpoints include patient-reported outcomes on quality of life measures, treatment adherence, and AEs [ 57 ].…”
Section: Emerging Data On the Efficacy Of Cladribine Tabletsmentioning
confidence: 99%